Maffucci syndrome - Widhodho T. Karyomanggolo; Dyani Kusumowardhani (Indonesian Pediatric Society, 1999)
A case of Maffucci syndrome was found in a 6 year old Indonesian girl.Her first sign of bone malformation was noticed on her right arm at the age of 7 months, but since there were no other complaint, such as pain or dysfunction, no further investigation was done. The complaints that brought her to Cipto Mangunkusumo Hospital, Jakarta, were an incomplete cleft palate and right axillary masses which were then known as cavernous hemangiomas. On physical examination another hemangioma was found on the major labia fold. From bone survey, generalized enchondromatosis was recognized and bone biopsy was then scheduled, bu t when the incision was done another hemangioma was found, so biopsy wascanceled due to risk of bleedings. Magnetic resonance imaging of the right humerus reaflirmed that the mass inside the bone was enchondroma and the masses in the axilla were subcutaneous hemangioma. Radiologic bone examination done 2 years later revealed that the enchondromatosis had increased in size and spreading. IQ test s howed a borderline stage of intelligence, but there were no evidence of relationship with the disease.